Pengaruh Pengaturan Pergerakan sebagai Pembentuk Image Kawasan Wisata: Studi Kasus: Puncak Sosok Bantul - Irwin Panjaitan (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2022)
Title: Circulation Settings, Route Design as an Image Branding on Tourism Destination/Areas (Case Study: Puncak Sosok Bantul) Human being has memories, that shaped and accumulated from the previous experience with a strong impression. Through the impressions, someone would read a distinctive character of a place that might be liked or not. In a tourism destination , branding is an effort to make distinctive character of a tourist attraction marketable, and could be accepted by the visitors. Using the appropriate branding could make a visitor feel the impression of the tourism destination. This can lead into the image branding of the tourism destination to be discovered , experienced and enjoyed by visitors. Access route or pathway is one of the important components of circulation setting which later can shape the image branding of the destination. Puncak Sosok is one of the tourist attractions in the Bantul Regency area which is develop quite significantly. To improve the image quality of the Puncak Sosok tourism area, a simulation has been done for the circulation settings based on the principle of the relationship between the route/pathway and the other elements design. The method used is descriptive qualitative which makes it possible to explain the relationship between the circulation settings and the image of the Puncak Sosok tourism area.